Theorists' Theories of Evaluation: A Conversation with Jennifer Greene - Michele Tarsilla (The Evaluation Center at Western Michigan University, 2010)
Background: Evaluation is sometimes viewed as a professional practice rather than a discipline corresponding to a well defined set of theories. However, Shadish, Cook and Leviton (1991) were able to demonstrate that evaluators' work does have theoretical foundations. In particular, the authors identified five main elements for evaluation theory and described the contribution made to each of them by seven of the most influential scholars in the field over the last five decades. Purpose: This paper intends to further the discussion on evaluation theory, by examining some of the contributions made Jennifer Greene, one of the most influential figures in contemporary evaluation. The paper mainly focuses on Greene's innovative ideas on each of the five main elements of evaluation theory. Setting: Not applicable. Subjects: Not applicable. Research Design: Not applicable. Data Collection and Analysis: The paper is the result of a desk review of Jennifer Greene's most relevant work on bias, objectivity, and advocacy in evaluation and a phone interview with her. For the sake of accuracy, the text of the interview and the corresponding analysis were submitted to Greene for review prior to publication. Findings: The author shows how Greene has incorporated the five principles into her own work and how this eventually influenced her practice. Greene sorts evaluation approaches based on the interests they serve and the values they promote. However, she seems to have developed her theory on valuing further over the years and today she claims that evaluators should never privilege anyone's specific side in the course of their assignments. Second, as knowledge is mediated by evaluators' perceptual frames, Greene believes that an unfiltered (objective) view of the world is not feasible. Third, she views evaluation as a force for democratizing public conversations about important issues. Fourth, although the evaluator's relationship with program staff could be collegial, Greene believes that evaluators have no authority or responsibility for the program design and implementation. Fifth, Greene declares that advocacy in evaluation is inevitable and, as a result, evaluators should play a socially enfranchising role today. Conclusions: The debate on evaluation's main theoretical foundations is still relevant. For this purpose, the author recommends that the five main theories applied by this article to examine Jennifer Greene's work should be used more systematically in the future to describe and analyze evaluators' practice. Such theoretical categories would be especially beneficial in that they will provide some common ground of understanding among both practitioners and scholars on evaluation concepts and practices which experience has shown to be in constant evolution.